(untitled) (Altre Modernità, 2020)
Since the end of the Nineteenth Century the hysterical body has progressively invaded the medical and artistic European scene, giving birth to different kinds of ambivalent performances. On the one hand, the ’staging’ of hysteria represented the attempt of power to reject the sick subject in order to cure his or her pathology and protect the collectivity by defusing its mechanism of sick mimesis. On the other hand, the hysterical body started to be investigated and performed also by the performing arts, which considered it as a manifestation of a positive and creative kind of performance: a physical-verbal alternative, a gestural language as well as a form of social iconic communication. As a consequence, the theatre scene grew more "nervous" and sick, while the most important performers of the period became more and more similar to the hysterics immortalized by medical photos. The pathological gesture prevailed and, as a consequence, theatre was obliged to deflagrate into new and hybrid languages. Thanks to its polarity, the hysterical body, sick or misshapen - an upsetting but, at the same time, attractive object - was expressed by a pantomimic and grotesque type of staging - the Grand-Guignol - which promoted a gratifying performance of pathology. By adapting to the times and changing its shape, hysteria passed into Antonin Artaud’s body-theatre. Nowadays, its pathological gesture seems to have been scientifically subdued and reabsorbed into the norm of bodies.